2011
DOI: 10.1080/08927014.2011.577525
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection of bacterial biofilms in pilot-scale cooling tower systems

Abstract: The impact of continuous chlorination and periodic glutaraldehyde treatment on planktonic and biofilm microbial communities was evaluated in pilot-scale cooling towers operated continuously for 3 months. The system was operated at a flow rate of 10,080 l day−1. Experiments were performed with a well-defined microbial consortium containing three heterotrophic bacteria: Pseudomonas aeruginosa, Klebsiella pneumoniae and Flavobacterium sp. The persistence of each species was monitored in the recirculating cooling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…They are major sources of nosocomial pneumonias and bacteremia from hospital devices and water supply systems, and they have been found to be major contributors of biofilms associated with outbreaks of Legionellosis (Stamm et al ., ; Orrison et al ., ; Pearson et al ., ; Anaissie et al ., ). These two organisms have previously been used to form a well‐defined consortium with Klebsiella pneumoniae to examine the survival and growth of Legionella pneumophila in biofilms (Murga et al ., ) and to study biofilm colonization and disinfection in pilot‐scale cooling tower systems (Liu et al ., , ). Pseudomonas aeruginosa has been observed to dominate the community in closed batch systems, while Flavobacterium has been found to dominate in open (flow‐through) systems (Liu et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…They are major sources of nosocomial pneumonias and bacteremia from hospital devices and water supply systems, and they have been found to be major contributors of biofilms associated with outbreaks of Legionellosis (Stamm et al ., ; Orrison et al ., ; Pearson et al ., ; Anaissie et al ., ). These two organisms have previously been used to form a well‐defined consortium with Klebsiella pneumoniae to examine the survival and growth of Legionella pneumophila in biofilms (Murga et al ., ) and to study biofilm colonization and disinfection in pilot‐scale cooling tower systems (Liu et al ., , ). Pseudomonas aeruginosa has been observed to dominate the community in closed batch systems, while Flavobacterium has been found to dominate in open (flow‐through) systems (Liu et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…At 360 h of incubation, yeasts were included into a mature biofilm and this status certainly explains the increased resistance of yeasts to chlorine. The greater efficacy of chlorine on planktonic compared to sessile microorganisms has been widely shown with other microbial species (Karpay et al ., ; Steed & Falkinham, ; Liu et al ., ). Only concentrations of 62 and 118 μg mL −1 of chlorine were shown to be completely effective against C. albicans whatever their age at the time of the treatment, preventing any growth of yeasts (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…This bacterium has been associated with early stages of biofilm formation in metallic material surfaces (Doğruöz et al 2009b;Liu et al 2009Liu et al , 2011; their primary role appears to be the establishment of an oxygen-free environment to harbor other potentially corrosive bacteria with diverse oxidative profiles (Pedersen et al 1988). They also produce exopolysaccharides, which protect cells from metallic ions and help to trap other species of microorganisms (Gubner and beech 2000;Ceyhan and Ozdemir 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Besides total heterotrophic bacteria, Pseudomonas aeruginosa was chosen because it has been extensively studied and associated with biofilms and to compare the system in this study to those of other researchers who reported the efficacy of diverse biocides in the control of microbiota using P. aeruginosa biofilms (Costerton 1999;Moreno et al 1993;Ceyhan andOzdemir 2008, Blasco et al 2008;Liu et al 2009Liu et al , 2011. For monitoring sessile bacteria, glass surfaces were also used along with stainless and carbon steel coupons; also, corrosion coupons and linear polarization resistance (LPR) probes were used for monitoring corrosion in the two cooling towers.…”
Section: Introductionmentioning
confidence: 99%